Respuestas

2012-10-24T19:31:10+02:00

       Vf  -  V i

A =  ======     aceleración                                                                Vf  -  V i

              T                                                                                  t  =  ======    

                                                                                                              a

           

 

     

X =   Vi * T + a * t2/ 2            X = distancia

 

 

          Vf  +  V i

 X  =  ========  * t   

                2

 

2 * a * t = V2- Vi2         de esta fórmula se derivan otras

 

        V2- Vi2        

T =  ======

           2 * a

 

 

        V2- Vi2        

A  =  ======

           2 * t

 

espero te sirva

2012-10-24T22:50:50+02:00

MRUA

V=Vo+at

S=So+Vo x t + 1/2 x a x tcuadrado

Vcuadrado= Vo cuadrado + 2 x a x s 

 

*x= multiplicado por